Brutalist Practice in 1960’s Berlin Churches: Experimental Interior Spaces - Özlem Balcı Öztürk; Oya Şenyurt (Histories of Postwar Architecture)
Numerous buildings, especially religious buildings, were destroyed and damaged in Europe during the Second World War. The city of Berlin is among those that suffered losses. Repairing the damage to churches that have a place in the collective memory and designing new churches played a crucial role in helping people hold on to life again. In the 1960s, new church construction in West Berlin experienced its pick. In this period, which Goldhagen describes as an interregnum between an expiring Modernism and dawning Postmodernism, experimental designs emerged under the influence of Brutalism. This study focuses on brutalist churches built in Berlin in the 1960s: Kaiser Wilhelm Memorial Church, Maria Regina Martyrum Memorial Church, and Paul Gerhardt Church. Defining a point of identity for the city, these churches not only represent a point of social unification for the community but also aim to strengthen the faith. It is possible to capture the same spiritual effect in the blue light leaking from the concrete modules in Kaiser Wilhelm Memorial Church, the light shining through the concrete beams in Maria Regina Martyrum Memorial Church, and the colors reflected from the stained glass in Paul Gerhardt Church. The role of religious buildings in the post-war Berlin brutalist practice, design parameters in the context of Reyner Banham's principles, and the spiritual effect of light were discussed through literature, periodicals, and visuals obtained through on-site documentation.